Influence of the Secondary Cell Wall Polymer on the Reassembly, Recrystallization, and Stability Properties of the S-Layer Protein from Bacillus stearothermophilus PV72/p2 - Sára, Margit (American Society for Microbiology, 1998)
The high-molecular-weight secondary cell wall polymer (SCWP) from Bacillus stearothermophilus PV72/p2 is mainly composed of N-acetylglucosamine (GlcNAc) and N-acetylmannosamine (ManNAc) and is involved in anchoring the S-layer protein via its N-terminal region to the rigid cell wall layer. In addition to this binding function, the SCWP was found to inhibit the formation of self-assembly products during dialysis of the guanidine hydrochloride (GHCl)-extracted S-layer protein. The degree of assembly (DA; percent assembled from total S-layer protein) that could be achieved strongly depended on the amount of SCWP added to the GHCl-extracted S-layer protein and decreased from 90 to 10% when the concentration of the SCWP was increased from 10 to 120 μg/mg of S-layer protein. The SCWP kept the S-layer protein in the water-soluble state and favored its recrystallization on solid supports such as poly-l-lysine-coated electron microscopy grids. Derived from the orientation of the base vectors of the oblique S-layer lattice, the subunits had bound with their charge-neutral outer face, leaving the N-terminal region with the polymer binding domain exposed to the ambient environment. From cell wall fragments about half of the S-layer protein could be extracted with 1 M GlcNAc, indicating that the linkage type between the S-layer protein and the SCWP could be related to that of the lectin-polysaccharide type. Interestingly, GlcNAc had an effect on the in vitro self-assembly and recrystallization properties of the S-layer protein that was similar to that of the isolated SCWP. The SCWP generally enhanced the stability of the S-layer protein against endoproteinase Glu-C attack and specifically protected a potential cleavage site in position 138 of the mature S-layer protein.